The Southernmost bear: Pararctotherium (Carnivora, Ursidae, Tremarctinae) in the latest Pleistocene of Southern Patagonia, Chile - Morello, Flavia (2003)
A second upper incisor belonging to the tremarctine bear Pararctotherium was recovered from latest Pleistocene deposits in Cueva de los Chingues, Magallanes, Chile (San Roman et al., 2000). This is the southernmost record of an ursid in the world and one of the youngest records of Pararctotherium. The paleoenvironment of southern Patagonia in the latest Pleistocene (ca. 11,000 yBP) was a cold grassland.